2019
DOI: 10.1111/pre.12396
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequencing and anatomy demonstrate that Pacific Codium simulans is a genetically variable species found in the floras of Bermuda and Florida

Abstract: SUMMARY When DNA sequences from Bermuda plants described as Codium isthmocladum ssp. clavatum and a recent collection from Florida originally thought to be C. decorticatum were analyzed, they were found to be a genetic match to the Pacific Mexican species C. simulans. Historical voucher collections assigned to C. isthmocladum ssp. clavatum show that this Pacific lineage has been present in Bermuda (Atlantic) waters for over a century, thus precluding a very recent introduction from the Pacific. We hypothesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…clavatum) is reported from 67-73 m depths (Norris and Olsen 1991), and in Brazil it is reported at 75 m depths (Joly and Yoneshigue Braga 1966). Schneider et al (2020) demonstrated that Bermudan species historically treated as Codium isthmocladum subsp. clavatum molecularly conformed to Codium simulans from Pacific Mexico.…”
Section: Figure 26mentioning
confidence: 99%
See 1 more Smart Citation
“…clavatum) is reported from 67-73 m depths (Norris and Olsen 1991), and in Brazil it is reported at 75 m depths (Joly and Yoneshigue Braga 1966). Schneider et al (2020) demonstrated that Bermudan species historically treated as Codium isthmocladum subsp. clavatum molecularly conformed to Codium simulans from Pacific Mexico.…”
Section: Figure 26mentioning
confidence: 99%
“…clavatum molecularly conformed to Codium simulans from Pacific Mexico. Codium simulans is now considered to be both a morphologically (Pedroche et al 2002) and genetically (Schneider et al 2020) variable species. [Illustrations: as Codium isthmocladum subsp.…”
Section: Figure 26mentioning
confidence: 99%